Macroeconomic effects of currency devaluation a case study of Bangladesh - Nag, Nitai C. (1990)
The hypotheses of contractionary effects of devaluation have been tested with the hel[ of a small macroeconometric model of the economy of Bangladesh. Although highly contractionary supply-side effects are observed, devaluation has been found to expand output modestly through the demand side. Devaluation, however, improves the current account of the balance of payments. A devaluation cum credit contraction improves trade balance; however, the accompanying hazards are contraction in output, consumption, investment, export, and import on the one hand, and an alarmingly high proportionate rise in price level, on the other. In other words, devaluation-cum-credit-contraction is stagflationary. The redistributive effects of a stereotype devaluation-based stabilization policy may pro9ve to be destabilizing for a very poor country.
Keywords: Devaluation of currency -- Bangladesh